A comparative study of the effect of multiple immersions on Aedini (Diptera: Culicidae) mosquito eggs with emphasis on sylvan vectors of yellow fever virus - Alencar, Jerónimo (2014)
The effect of multiple immersions on Haemagogus janthinomys, Haemagogus leucocelaenus, Aedes albopictus and Ochlerotatus terrens eggs was studied. Eggs were collected in April, June, October and December of 2011 in Minas Gerais, Brazil. Most of the Aedes and Ochlerotatus eggs hatched upon the first immersion, while Haemagogus eggs showed a varied instalment hatching response. The number of immersions required for hatching increased for eggs collected closer to the dry winter season.